Design and implementation of a series switching SPSI for PV cell to use in carrier based grid synchronous system - Tawfikur Rahman; S. M. A. Motakabber; Muhammad I. Ibrahimy; A. H. M. Zahirul Alam (Institute of Advanced Engineering and Science, 2019)
A carrier-based grid synchronous method is proposed to develop the system efficiency, phase and power quality of the inverter output waves. The operating principle of a single-phase phase synchronous inverter (SPSI) is introduced, with proper synchronous paid to the switching-frequency synchronizing voltage made by the interleaved process, as well as actual mitigation approaches. In the construction of the SPSI, input and output filters are electrically coupled with the two sides of an inverter. The inverter power electronic switches and other electrical components are operated by carrier-based grid synchronous controller (CBGSC) with PWM regulator. The SPSI is designed and implemented with the Toshiba 40WR21 IGBT, Digital Microcontroller pulse controller (DMPC) and 4N35 Optocoupler with a fundamental frequency of 50Hz. The other parameters are considered as load resistance, =11Ω, duty cycle, 85%, carrier frequency, 2.5kHz and input DC voltage, ± 340V. In addition, LCL lowpass grid filters are used to convert squire wave to sine wave with required phase and frequency. Finally, the simulated and experimental results obtained with a carrier-based grid synchronous SPSI experimental prototype are exposed for justification, showing the phase error of 55% improvement, reduced 11% of THD and the conversion efficiency of 97.02% highly predicted by the proposed design technique to improve the microgrid system.